Math, asked by appkappo11, 9 months ago

solve using identities 8x³ + 27y³​

Attachments:

Answers

Answered by my069234
0

Answer:

Use here identitiey( a+ b)^3.

and one more THING why u use your photo.

Answered by Anonymous
3

Answer:

Here is the answer =>

Step-by-step explanation:

 {8x}^{3}  +  {27x}^{3}  =  ({2x})^{3}  +  ({3y})^{3}

 ({2x})^{3}  +  ({3y})^{3}  = (2x + 3y)( {2x}^{2}  - 6xy +   {3y}^{2}

as \:  {a}^{3}   +  {b}^{3}  = (a + b)( {a}^{2}  - ab +  {b}^{2})

HOPE IT HELPS.

Similar questions